Edaphic and climatic factors that affect intake and selectivity of forage plants under grazing - Lascano Aguilar, Carlos Eduardo (International Center for Tropical Agriculture, 1993)
The effect that fertilization and season have on intake and acceptability of forage species is reviewed. From this review one concludes that a positive effect can be achieved on the intake and acceptability of some grasses and legumes by fertilizing with superphosphate or with calcium and sulfur. Some of the papers reviewed associate this effect with the correction of mineral deficiencies, with changes in plant growth and morphology, and with the reduction of certain chemical components such as tannins. The season markedly influences the selection animals make in legume-grass associations, the selection being more toward legume in the dry season when the grass loses its quality, as compared with the wet season when grass is preferred. Preference tests should be included in the legume evaluation sequence, so to detect, early on, those species or accessions with palatability problems. Such tests would also help determine the possible influence of fertilization on acceptability. Finally, the effect of season on animal selectivity on grass-legume associations should also be evaluated under small-plot grazing. This would help define more clearly the type of management that an association should have in a given ecosystem.